107k views
3 votes
How do you solve the equations if the exponent is negative

How do you solve the equations if the exponent is negative-example-1
User ThdK
by
5.7k points

1 Answer

3 votes

ANSWER

A. 1/9

Step-by-step explanation

When we have an expression with a negative exponent we can solve it by "flipping" the fraction and solving with the positive exponent:


\mleft((a)/(b)\mright)^(-c)=\mleft((b)/(a)\mright)^c

In this problem we have to find:


f(-2)=3^(-2)

We can think of a whole number as a fraction whose denominator is 1:


f(-2)=\mleft((3)/(1)\mright)^(-2)

So we can use the trick:


f(-2)=\mleft((1)/(3)\mright)^2

And solve:


f(-2)=(1)/(3^2)=(1)/(9)

User Facundo Casco
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.